Murder at Yellowstone City [videorecording (DVD)] - Belgau, Eric; Byrne, Gabriel, 1950-; Jane, Thomas; Mustafa, Isaiah, 1974-; Camp, Anna, 1982-; Wolff, Nat, 1994-; Dreyfuss, Richard; Thompson, Scottie, 1981-; Garcia, Aimee, 1978-; Beatty, Tanaya; McGowan, Zach; Ales, John; et al. (RLJ Entertainment, Inc., 2022)
In a gold-rush boomtown that has gone bust, a prospector strikes gold - and is murdered. Sheriff James Ambrose assumes the killer to be a newcomer, a former enslaved person who calls himself Cicero. But as it becomes clear that Cicero is innocent, and as the mystery of the prospector's death deepens and puts the whole town in jeopardy, the town's new minister, Thaddeus Murphy must stand up to Sheriff Ambrose and bring the true culprit to justice.